PENGARUH TERPAAN IKLAN SHOPEE DI TELEVISI DAN INTERAKSI REFERENCE GROUP TERHADAP MINAT BERTRANSAKSI SECARA ONLINE - Tiara Tanca, Jhenika; Budi Lestari, Sri (Interaksi Online, 2018)
In Indonesia, the growth of e-commerce is grown rapidly use for human daily needs. One of the e-commerce companies in Indonesia is Shopee. To attract and seize their consumer, they used advertising as their promotion tools. In fact, Shopee is one of the e-commerce which often appear in television. Beside that, the number of people downloading the Shopee application has increased more than 100% on 2015-2018 period. Based on that explanation above, this research will discuss about the influence of Advertising Exposure of Shopee on Television Toward The Intention in Online Transacting. In addition to advertising exposure, this research will discuss about reference group interaction as well. This research used Strong Advertising Theory and Darley, Blankson and Luethge’s Model. The population of this research are men and women in the age of 18 until 30, who domicile in Semarang and have experienced in watching the Shopee advertisement on television. The sum of sample are 50 which have been taken by purposive sampling technique. Analysis of the data is used multiple linear regression with computer analized by IBM SPSS. The result of the first hypotesys shows that the advertising exposure of Shopee on television is significantly influencing towards the intention of online transacting with regression coefficient 0.603 meaning that every variable increment of advertising exposure of shopee on television (X1) is 1 unit. Hence, the variable of intention in online transacting (Y) is increased by 0.603, as well. Besides that, the variable of the advertising exposure of shopee on television has that impact by 60.3% towards the variable of the intention in online transacting. The Significance value X1 (0.047 < 0.050) so that the advertising exposure of shopee on television takes charge in affecting the intention in online transacting of a customer. The result of the second hypotesys shows that reference group interaction is significantly influencing towards the intention of online transacting with regression coefficient 0.755 meaning that every variable increment of reference group imteraction (X2) is 1 unit. Hence, the variable of intention in online transacting (Y) is increased by 0.755 as well. Besides that, the variable of reference group interaction has that impact by 75.5% towards the variable of the intention in online transacting. The Significance value X2 (0.031 < 0.050) so that the reference group interaction takes charge in affecting the intention in online transacting of a customer.